RETRACTED: Biotechnology factors influence on formation of curd cheese quality indicators - Trukhachev Vladimir; Yankovskaya Valentina; Shipilov Andrey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001